Proteoglycans—Biomarkers and Targets in Cancer Therapy - Nikitovic, Dragana; Berdiaki, Aikaterini; Spyridaki, Ioanna; Krasanakis, Theodoros; Tsatsakis, Aristidis; Tzanakakis, George N. (Frontiers in Endocrinology, 2018)
Proteoglycans (PGs), important constituents of the extracellular matrix (ECM), have been associated with cancer pathogenesis. Their unique structure consisting of a protein core and glycosaminoglycan chains endowed with fine modifications, constitutes these molecules as capable cellular effectors important for homeostasis and contributing to disease progression. Indeed, differential expression of PGs and their interacting proteins has been characterized as specific for disease evolvement in various cancer types. Importantly, PGs to a large extent regulate the bioavailability of hormones, growth factors and cytokines as well as the activation of their respective receptors which regulate phenotypic diversibility, gene expression and rates of recurrence in specific tumor types. Defining and targeting these effectors on an individual patient basis offers ground for the development of newer therapeutic approaches which may act as either supportive or a substitute treatment to the standard therapy protocols. This review discusses the roles of PGs in cancer progression, developing technologies utilized for the defining of the PG “signature” in disease and how this may facilitate the generation of tailor-made cancer strategies.